The Science Process Skills Of Class B Children Reviewed from The Decision-Making Learning Model at TK ABA Rendeng, Purworejo City - Syarifah, Ihda; Tasuah, Neneng (BELIA: Early Childhood Education Papers, 2018)
This research is done based on the phenomenon at TK (Kindergarten) ABA Rendeng, Purworejo City where children are not used to communicating what they see, the minimal use of tools and materials during the learning process, models and variations of learning that are not appropriate with the material and often using media images or through worksheets. From these problems it will result in children having difficulty drawing conclusions, lack of understanding of children, children are often not interested in science activities, and children feel bored. This study aims to prove whether there are differences and  improvement in science process skills after being given a decision-making learning model. The population of this study is all students with total 50. The sample is 31 students from the total population that are taken by cluster sample technique. This study uses an experimental model with a one-group pretest-posttest design technique. The results of the calculation of the t-test have obtained the value of t-count = 2.042 with sig = 0.000 so Ha is accepted. This proves that there are significant differences regarding the class B child science process skills in terms of giving treatment by using decision-making learning models. From the test results using the percentage technique, there is an increase in children's science skills in class B, as seen from the percentage increase in pretest and posttest data of 32.2%